Image forming apparatus, image forming method, and process cartridge

By employing a controlled particle diameter range for polytetrafluoroethylene and strontium titanate in the electrophotographic photoreceptor's surface layer, the issue of uneven image density in pattern images is resolved, ensuring stable chargeability and consistent output.

JP7602972B2Active Publication Date: 2024-12-19CANON KK
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021102049
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-18
Publication Date
2024-12-19
Estimated Expiration
2041-06-18

AI Technical Summary

Technical Problem

Existing image forming technologies using organic photoreceptors experience uneven image density over time, particularly when outputting pattern images for extended periods, due to detachment of polytetrafluoroethylene particles affecting chargeability.

Method used

The use of an electrophotographic photoreceptor with a surface layer containing polytetrafluoroethylene particles and strontium titanate particles, where the number average particle diameters are controlled within specific ranges to stabilize chargeability and prevent density unevenness.

Benefits of technology

The solution effectively maintains consistent image density over long-term pattern image output by stabilizing chargeability through controlled particle detachment and retention, preventing unevenness in image density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602972000016
    Figure 0007602972000016
  • Figure 0007602972000017
    Figure 0007602972000017
  • Figure 0007602972000018
    Figure 0007602972000018
Patent Text Reader

Abstract

To suppress unevenness of image density in a half tone image after elapse of a long period of time since a pattern image was output.SOLUTION: An image formation device includes an electrophotographic photoreceptor, a surface layer of which includes: a charge transporting compound having a chain polymerizable functional group or a successive polymerizable functional group; and polytetrafluoroethylene particles. Primary particles of the polytetrafluoroethylene particles have a number average particle size of 165 nm or more and 185 nm or less. Primary particles of strontium titanate particles on a toner surface have a number average particle size of 20 nm or more and 70 nm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an image forming apparatus, an image forming method, and a process cartridge. [Background technology]

[0002] In recent years, organic photoreceptors have been widely used as electrophotographic photoreceptors mounted on electrophotographic devices. In recent years, there has been a demand for improving the mechanical durability (wear resistance) of electrophotographic photoreceptors and improving lubricity for improved cleanability in order to extend the life of electrophotographic photoreceptors and improve image quality during repeated use. Providing a curable surface layer (protective layer) is effective in improving the wear resistance of electrophotographic photoreceptors. Patent Document 1 discloses a technology for improving cleanability by incorporating polytetrafluoroethylene particles into the surface layer (protective layer). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2013-148792 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, there are cases where the above techniques fail to maintain high image quality. When a halftone image having a uniform surface is output over the entire surface after a specific pattern image has been output for a long period of time, uneven image density may occur.

[0005] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide an image forming apparatus which does not cause uneven image density even when pattern images are output for a long period of time. [Means for solving the problem]

[0006] The above object can be achieved by the present invention described below. That is, an electrophotographic photoreceptor having a support, a photosensitive layer, and a surface layer; a charging means for charging the surface of the electrophotographic photoreceptor; an image exposure means for irradiating the charged surface of the electrophotographic photosensitive member with image exposure light to form an electrostatic latent image on the surface of the electrophotographic photosensitive member; a developing means having a toner and for developing the electrostatic latent image with the toner to form a toner image on the surface of the electrophotographic photoreceptor; a transfer means for transferring the toner image from the surface of the electrophotographic photoreceptor to a transfer material; a cleaning means for removing residual toner remaining on the surface of the electrophotographic photoreceptor after transfer by a cleaning blade; a fixing means for fixing the toner image transferred onto the transfer material; An image forming apparatus having The surface layer is a charge transporting compound having a chain polymerizable functional group or a step-polymerizable functional group; Polytetrafluoroethylene particles and A cured film obtained by curing a composition comprising: The number average particle diameter of the primary particles of the polytetrafluoroethylene particles is 165 nm or more and 185 nm or less, The toner comprises toner particles and strontium titanate particles present on the surfaces of the toner particles, and the number average particle diameter of the primary particles of the strontium titanate particles is 20 nm or more and 70 nm or less. Effect of the Invention

[0007] According to the present invention, it is possible to provide an image forming apparatus in which image density unevenness does not occur even when pattern images are output for a long period of time. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic diagram illustrating an example of a configuration of an electrophotographic photoreceptor of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of a chart used in the evaluation. [Diagram 3] FIG. 1 is a diagram showing an example of a schematic configuration of an electrophotographic apparatus equipped with a process cartridge having an electrophotographic photosensitive member of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described in detail below with reference to preferred embodiments. The image forming apparatus of the present invention comprises an electrophotographic photoreceptor having a support, a photosensitive layer and a surface layer, charging means for charging the surface of the electrophotographic photoreceptor, image exposure means for irradiating the charged surface of the electrophotographic photoreceptor with image exposure light to form an electrostatic latent image on the surface of the electrophotographic photoreceptor, developing means having a toner and developing the electrostatic latent image with the toner to form a toner image on the surface of the electrophotographic photoreceptor, transfer means for transferring the toner image from the surface of the electrophotographic photoreceptor to a transfer material, cleaning means for removing residual toner remaining on the surface of the electrophotographic photoreceptor after transfer with a cleaning blade, and a toner image removing means for removing residual toner from the surface of the electrophotographic photoreceptor after transfer with a cleaning blade. and a fixing means for fixing the transferred toner image to the transfer material, wherein the surface layer is a cured film formed by curing a composition containing polytetrafluoroethylene particles and a charge transport compound having a chain polymerizable functional group or a step-polymerizable functional group, the number average particle diameter of primary particles of the polytetrafluoroethylene particles is 165 nm or more and 185 nm or less, and the toner has toner particles and strontium titanate particles present on the surfaces of the toner particles, the number average particle diameter of primary particles of the strontium titanate particles is 20 nm or more and 70 nm or less.

[0010] The mechanism by which the configuration of the image forming apparatus according to one aspect of the present invention solves the problems is believed to be as follows. The surface of the photoreceptor contains polytetrafluoroethylene particles (PTFE particles) to improve lubricity and durability. When image output continues, the polytetrafluoroethylene particles protruding from the surface layer of the photoreceptor may become detached. Suppose a pattern image such as that shown in Figure 2(a) is output for a long period of time. In this case, it is thought that there will be more detachment of polytetrafluoroethylene particles from the surface layer of the photoreceptor corresponding to areas with high density in the output image, and less detachment of polytetrafluoroethylene particles from the surface of the photoreceptor corresponding to areas with low image density. It is believed that the difference in the detachment of polytetrafluoroethylene particles causes a difference in the chargeability of the photoconductor, which results in uneven density when a halftone image is output.

[0011] As a result of intensive research by the present inventors, the following was found regarding the image density unevenness that occurs when a pattern image is output for a long period of time. That is, it was found that controlling the number average particle diameter of the primary particles of the polytetrafluoroethylene particles contained in the surface layer of the electrophotographic photoreceptor and the number average particle diameter of the primary particles of strontium titanate, which is a type of inorganic particle externally added to the toner particles, is effective in suppressing unevenness. It is effective to set the number average particle diameter of the primary particles of the polytetrafluoroethylene particles to 165 nm or more and 185 nm or less, and the number average particle diameter of the primary particles of the strontium titanate particles to 20 nm or more and 70 nm or less. It is considered that by doing so, the strontium titanate particles externally added to the toner surface can easily enter and be held in the holes formed by the detachment of the polytetrafluoroethylene particles on the surface of the electrophotographic photoreceptor. Although the detailed mechanism is speculation, it is considered that the fluctuation in chargeability is suppressed by holding the strontium titanate particles instead of the polytetrafluoroethylene particles, and therefore the density unevenness of the image is suppressed.

[0012] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, an embodiment of the present invention will be described in detail. [Electrophotographic photoreceptor] The electrophotographic photoreceptor in this embodiment has a support, a photosensitive layer, and a surface layer. A more preferred embodiment is one in which a support, an undercoat layer, a charge generating layer, a charge transport layer and a surface layer are laminated in this order.

[0013] Fig. 1 is a diagram showing an example of the layer structure of an electrophotographic photoreceptor of the present invention, in which an undercoat layer 102, a charge generating layer 103, a charge transport layer 104, and a surface layer 105 are laminated on a support 101. The method for producing the electrophotographic photoreceptor of the present invention includes a method of preparing the coating liquid for each layer described later, coating the layers in the desired order, and drying the liquid. In this case, the coating liquid can be applied by dip coating, spray coating, inkjet coating, roll coating, die coating, blade coating, curtain coating, wire bar coating, ring coating, etc. Among these, dip coating is preferred from the viewpoints of efficiency and productivity.

[0014] Each of the components, such as the support, the conductive layer, the undercoat layer, the charge generating layer, the charge transport layer, and the surface layer (protective layer), will be described below.

[0015] <Support> The support is preferably one having electrical conductivity (conductive support). The shape of the support may be cylindrical, belt-like, sheet-like, or the like. Among them, the cylindrical shape is preferable. The surface of the support may be subjected to electrochemical treatment such as anodization, blasting, cutting, or the like. The material of the support is preferably metal, resin, glass, or the like. Examples of metals include aluminum, iron, nickel, copper, gold, stainless steel, and alloys thereof, with aluminum being preferred. Furthermore, when the base material is a resin or glass, it is preferable that the base material is imparted with electrical conductivity by being mixed with or coated with an electrically conductive material.

[0016] <Conductive layer> In the present invention, a conductive layer may be provided on the support. By providing the conductive layer, scratches and irregularities on the surface of the support can be concealed and light reflection on the surface of the support can be controlled. The conductive layer preferably contains conductive particles and a resin.

[0017] Examples of materials for the conductive particles include metal oxides, metals, and carbon black. Examples of metal oxides include zinc oxide, aluminum oxide, indium oxide, silicon oxide, zirconium oxide, tin oxide, titanium oxide, strontium titanate, magnesium oxide, antimony oxide, bismuth oxide, etc. Examples of metals include aluminum, nickel, iron, nichrome, copper, zinc, silver, etc. Among these, it is preferable to use metal oxide particles that are conductive particles, and it is particularly preferable to use titanium oxide, tin oxide, and zinc oxide. When a metal oxide is used as the conductive particles, the surface of the metal oxide may be treated with a silane coupling agent or the like, or the metal oxide may be doped with an element such as phosphorus or aluminum or an oxide thereof.

[0018] The conductive particles may have a laminated structure having a core particle and a coating layer that covers the core particle. Examples of the core particle include titanium oxide, barium sulfate, zinc oxide, etc. Examples of the coating layer include metal oxides such as tin oxide. When a metal oxide is used as the conductive particles, the volume average particle size is preferably 1 nm or more and 500 nm or less, and more preferably 3 nm or more and 400 nm or less.

[0019] Examples of the resin include polyester resin, polycarbonate resin, polyvinyl acetal resin, acrylic resin, silicone resin, epoxy resin, melamine resin, polyurethane resin, phenol resin, and alkyd resin. The conductive layer may further contain silicone oil, resin particles, a masking agent such as titanium oxide, and the like.

[0020] The average thickness of the conductive layer is preferably from 1 μm to 50 μm, and particularly preferably from 3 μm to 40 μm.

[0021] The conductive layer can be formed by preparing a coating solution for the conductive layer containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. Examples of the dispersion method for dispersing the conductive particles in the coating solution for the conductive layer include a method using a paint shaker, a sand mill, a ball mill, and a liquid collision type high-speed disperser.

[0022] <Undercoat layer> In the present invention, an undercoat layer may be provided on the support or the conductive layer. By providing an undercoat layer, the adhesion between layers can be improved and a charge injection blocking function can be imparted.

[0023] The undercoat layer preferably contains a resin. Alternatively, the undercoat layer may be formed as a cured film by polymerizing a composition containing a monomer having a polymerizable functional group. Examples of the resin include polyester resin, polycarbonate resin, polyvinyl acetal resin, acrylic resin, epoxy resin, melamine resin, polyurethane resin, phenol resin, polyvinyl phenol resin, alkyd resin, polyvinyl alcohol resin, polyethylene oxide resin, polypropylene oxide resin, polyamide resin, polyamic acid resin, polyimide resin, polyamideimide resin, and cellulose resin. Examples of the polymerizable functional group contained in the monomer having a polymerizable functional group include an isocyanate group, a blocked isocyanate group, a methylol group, an alkylated methylol group, an epoxy group, a metal alkoxide group, a hydroxyl group, an amino group, a carboxyl group, a thiol group, a carboxylic anhydride group, and a carbon-carbon double bond group.

[0024] For the purpose of improving electrical properties, the undercoat layer may further contain an electron transporting material, a metal oxide, a metal, a conductive polymer, etc. Among these, it is preferable to use an electron transporting material or a metal oxide. Examples of the electron transport substance include a quinone compound, an imide compound, a benzimidazole compound, a cyclopentadienylidene compound, a fluorenone compound, a xanthone compound, a benzophenone compound, a cyanovinyl compound, an aryl halide compound, a silole compound, a boron-containing compound, etc. An electron transport substance having a polymerizable functional group may be used as the electron transport substance, and the undercoat layer may be formed as a cured film by copolymerizing the electron transport substance with the monomer having the polymerizable functional group described above. Examples of metal oxides include indium tin oxide, tin oxide, indium oxide, titanium oxide, strontium titanate, zinc oxide, aluminum oxide, silicon dioxide, etc. Examples of metals include gold, silver, aluminum, etc. The undercoat layer may further contain an additive.

[0025] The average thickness of the undercoat layer is preferably from 0.1 μm to 50 μm, more preferably from 0.2 μm to 40 μm, and particularly preferably from 0.3 μm to 30 μm.

[0026] The undercoat layer can be formed by preparing a coating solution for the undercoat layer containing the above-mentioned materials and solvent, forming a coating film from the coating solution, and drying and / or curing the coating solution. Examples of the solvent used in the coating solution include alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.

[0027] <Photosensitive layer> The photosensitive layer of an electrophotographic photoreceptor is mainly classified into (1) a multi-layer type photosensitive layer and (2) a single-layer type photosensitive layer. (1) The multi-layer type photosensitive layer has a charge generation layer containing a charge generation material and a charge transport layer containing a charge transport material. (2) The single-layer type photosensitive layer has a photosensitive layer containing both a charge generation material and a charge transport material.

[0028] (1) Laminated photosensitive layer The laminated type photosensitive layer has a charge generating layer and a charge transport layer.

[0029] (1-1) Charge generation layer The charge generating layer preferably contains a charge generating material and a resin.

[0030] Examples of the charge generating material include azo pigments, perylene pigments, polycyclic quinone pigments, indigo pigments, and phthalocyanine pigments. Among these, azo pigments and phthalocyanine pigments are preferred. Among phthalocyanine pigments, oxytitanium phthalocyanine pigments, chlorogallium phthalocyanine pigments, and hydroxygallium phthalocyanine pigments are preferred. The content of the charge generating material in the charge generating layer is preferably from 40% by mass to 85% by mass, and more preferably from 60% by mass to 80% by mass, based on the total mass of the charge generating layer.

[0031] Examples of the resin include polyester resin, polycarbonate resin, polyvinyl acetal resin, polyvinyl butyral resin, acrylic resin, silicone resin, epoxy resin, melamine resin, polyurethane resin, phenol resin, polyvinyl alcohol resin, cellulose resin, polystyrene resin, polyvinyl acetate resin, polyvinyl chloride resin, etc. Among these, polyvinyl butyral resin is more preferable.

[0032] The charge generating layer may further contain additives such as an antioxidant and an ultraviolet absorbing agent, etc. Specific examples of such additives include hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, and benzophenone compounds.

[0033] The average thickness of the charge generating layer is preferably from 0.1 μm to 1 μm, and more preferably from 0.15 μm to 0.4 μm.

[0034] The charge generating layer can be formed by preparing a coating solution for the charge generating layer containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, sulfoxide-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents.

[0035] (1-2) Charge transport layer The charge transport layer preferably contains a charge transport material and a resin.

[0036] Examples of the charge transport material include polycyclic aromatic compounds, heterocyclic compounds, hydrazone compounds, styryl compounds, enamine compounds, benzidine compounds, triarylamine compounds, and resins having groups derived from these materials. Among these, triarylamine compounds and benzidine compounds are preferred. The content of the charge transport material in the charge transport layer is preferably 25% by mass or more and 70% by mass or less, more preferably 30% by mass or more and 55% by mass or less, based on the total mass of the charge transport layer.

[0037] Examples of the resin include polyester resin, polycarbonate resin, acrylic resin, polystyrene resin, etc. Among these, polycarbonate resin and polyester resin are preferable. As the polyester resin, polyarylate resin is particularly preferable. The content ratio (mass ratio) of the charge transport material to the resin is preferably from 4:10 to 20:10, and more preferably from 5:10 to 12:10.

[0038] The charge transport layer may contain additives such as antioxidants, ultraviolet absorbers, plasticizers, leveling agents, slipping agents, and abrasion resistance improvers. Specific examples of the additives include the following: hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, siloxane-modified resins, silicone oils, fluororesin particles, polystyrene resin particles, polyethylene resin particles, silica particles, alumina particles, and boron nitride particles.

[0039] The average thickness of the charge transport layer is preferably from 5 μm to 50 μm, more preferably from 8 μm to 40 μm, and particularly preferably from 10 μm to 30 μm.

[0040] The charge transport layer can be formed by preparing a coating solution for the charge transport layer containing the above-mentioned materials and solvent, forming a coating film of this, and drying it. Examples of the solvent used in the coating solution include alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, and aromatic hydrocarbon-based solvents. Among these solvents, ether-based solvents or aromatic hydrocarbon-based solvents are preferred.

[0041] (2) Single-layer photosensitive layer The single-layer type photosensitive layer can be formed by preparing a coating solution for the photosensitive layer containing a charge generating material, a charge transporting material, a resin and a solvent, forming a coating film of this, and drying it. The charge generating material, the charge transporting material and the resin are the same as the examples of materials in "(1) Multi-layer type photosensitive layer" above.

[0042] <Surface layer> In the present invention, the electrophotographic photoreceptor has a surface layer. The surface layer is a layer located at the outermost surface of the layers of the electrophotographic photoreceptor. The surface of the surface layer is the surface of the electrophotographic photoreceptor. In the case of a laminated type photosensitive layer, the surface layer may be provided on the charge transport layer of the laminated type photosensitive layer, and in the case of a single-layer type photosensitive layer, the surface layer may be provided on the photosensitive layer.

[0043] The surface layer is a cured film obtained by curing a composition containing a charge transporting compound having a chain polymerizable functional group or a step-polymerizable functional group and polytetrafluoroethylene particles. Examples of the charge transporting compound having a chain polymerizable functional group and the charge transporting compound having a step-polymerizable functional group include the compounds represented by formula (a) or (b). [ka] (In formula (a), Ar 11 , Ar 12 , and Ar 13 represents a phenyl group or a biphenyl group which may have an alkyl group having 1 to 6 carbon atoms, an alkoxy group, a fluorine atom, a chlorine atom, a bromine atom, a hydroxy group, a hydroxymethyl group, or an alkoxymethyl group as a substituent. The alkyl group having 1 to 6 carbon atoms may be substituted with a (meth)acryloyloxy group. 11 , Ar12 , and Ar 13 may be the same or different.) [ka] (In formula (b), Ar 21 , Ar 22 , Ar 23 and Ar 24 represents a phenyl group which may have, as a substituent, an alkyl group having 1 to 6 carbon atoms, an alkoxy group, a fluorine atom, a chlorine atom, a bromine atom, a hydroxy group, a hydroxymethyl group, or an alkoxymethyl group, and the alkyl group having 1 to 6 carbon atoms may be substituted with a (meth)acryloyloxy group; Ar 25 and Ar 26 represents a phenylene group which may have an alkyl group having 1 to 6 carbon atoms as a substituent. 21 , Ar 22 , Ar 23 and Ar 24 may be the same or different. 25 and Ar 26 may be the same or different.)

[0044] Examples of the charge transporting compound having a chain polymerizable functional group include the formulae (1-1 to 1-12).

[0045] Examples of the charge transporting compound having a sequentially polymerizable functional group include the compounds represented by formulas (2-1 to 2-12).

[0046] [ka]

[0047] [ka]

[0048] [ka]

[0049] The surface layer coating liquid may contain a monomer having a polymerizable functional group in addition to the charge transporting compound. Examples of the polymerizable functional group of the monomer having a polymerizable functional group include an acryloyloxy group and a methacryloyloxy group. A material having a charge transport function may be used as the monomer having a polymerizable functional group. Examples of the reaction that may occur include a thermal polymerization reaction, a photopolymerization reaction, and a radiation polymerization reaction.

[0050] In the present invention, the surface layer contains polytetrafluoroethylene particles. The effects of the present invention can be obtained by making the number average particle diameter of the primary particles of the polytetrafluoroethylene particles 165 nm or more and 185 nm or less. It is more preferable that the proportion of polytetrafluoroethylene particles having a primary particle diameter of 150 nm or less is 10% or more, and that the proportion of particles having a primary particle diameter of 250 nm or more is 5% or less.

[0051] The content of polytetrafluoroethylene particles in the surface layer is more preferably 10% by mass or more and 40% by mass or less with respect to the total mass of the surface layer. When the content is in the range of 10% by mass or more and 40% by mass, it is believed that the strontium titanate can sufficiently fill the holes formed by the polytetrafluoroethylene particles being released, thereby further suppressing the change in the electrostatic charge.

[0052] The surface layer may contain additives such as antioxidants, ultraviolet absorbers, plasticizers, leveling agents, slippage imparting agents, and abrasion resistance improvers. Specific examples of additives include the following: hindered phenol compounds, hindered amine compounds, sulfur compounds, phosphorus compounds, benzophenone compounds, siloxane-modified resins, silicone oils, fluororesin particles, polystyrene resin particles, polyethylene resin particles, silica particles, alumina particles, and boron nitride particles.

[0053] The surface layer can further contain a charge transport material. Examples of the charge transport material include polycyclic aromatic compounds, heterocyclic compounds, hydrazone compounds, styryl compounds, enamine compounds, benzidine compounds, triarylamine compounds, and resins having groups derived from these materials. Among these, triarylamine compounds and benzidine compounds are preferred.

[0054] The average thickness of the surface layer is preferably from 0.5 μm to 10 μm, and more preferably from 1 μm to 7 μm.

[0055] The surface layer can be formed by preparing a coating solution for the surface layer containing the above-mentioned materials and solvent, forming this coating film on the photosensitive layer, and drying and / or curing it. Examples of the solvent used in the coating solution include alcohol-based solvents, ketone-based solvents, ether-based solvents, sulfoxide-based solvents, ester-based solvents, aliphatic halogenated hydrocarbon-based solvents, and aromatic hydrocarbon-based solvents. From the viewpoint of not dissolving the underlying photosensitive layer, alcohol-based solvents are preferred.

[0056] The coating film of the surface layer coating liquid can be cured by heat, ultraviolet light, and / or electron beams. In order to improve the strength of the surface layer of the electrophotographic photoreceptor and the durability of the electrophotographic photoreceptor, it is preferable to cure the coating film by ultraviolet light or electron beams. When irradiating with electron beams, examples of accelerators include scanning type, electrocurtain type, broad beam type, pulse type, laminar type, etc. The acceleration voltage of the electron beam is preferably 120 kV or less from the viewpoint of suppressing deterioration of material properties caused by the electron beam without impairing polymerization efficiency. In addition, the electron beam absorbed dose on the surface of the coating film of the coating solution for protective layer is preferably 5 kGy or more and 50 kGy or less, more preferably 1 kGy or more and 10 kGy or less.

[0057] In addition, when the composition is cured (polymerized) using an electron beam, it is preferable to irradiate the composition with the electron beam in an inert gas atmosphere and then heat the composition in an inert gas atmosphere, from the viewpoint of suppressing the polymerization inhibition action caused by oxygen. Examples of the inert gas include nitrogen, argon, and helium.

[0058] After irradiation with ultraviolet rays or electron beams, the electrophotographic photoreceptor is preferably heated to 100° C. or higher and 140° C. or lower, thereby obtaining a surface layer that has higher durability and suppresses image defects.

[0059] The surface of the surface layer may be subjected to surface treatment using an abrasive sheet, a shape transfer member, glass beads, zirconia beads, etc. Also, unevenness may be formed on the surface using a constituent material of the coating liquid. For the purpose of further stabilizing the behavior of the cleaning means (cleaning blade) that is brought into contact with the electrophotographic photosensitive member, it is more preferable to provide a concave or convex portion on the protective layer of the electrophotographic photosensitive member. The recesses or protrusions may be formed over the entire surface of the electrophotographic photoreceptor, or may be formed on a portion of the surface of the electrophotographic photoreceptor. When the recesses or protrusions are formed on a portion of the surface of the electrophotographic photoreceptor, it is preferable that the recesses or protrusions are formed over at least the entire contact area with the cleaning means (cleaning blade). When forming recesses or protrusions, a mold having protrusions corresponding to the recesses or a mold having recesses corresponding to the protrusions is pressed against the surface of the electrophotographic photosensitive member to transfer the shape, thereby forming recesses or protrusions on the surface of the electrophotographic photosensitive member.

[0060] [Process cartridges, electrophotographic devices] The process cartridge of the present invention integrally supports the electrophotographic photosensitive member described above and at least one means selected from the group consisting of a charging means, a developing means, a transfer means and a cleaning means, and is characterized in that the process cartridge is detachably mountable to the main body of the electrophotographic apparatus. The electrophotographic apparatus of the present invention is characterized by comprising the electrophotographic photosensitive member, charging means, image exposure means, developing means, transfer means, cleaning means and fixing means described above.

[0061] FIG. 3 shows an example of a schematic configuration of an electrophotographic apparatus having a process cartridge equipped with an electrophotographic photosensitive member. Reference numeral 1 denotes a cylindrical electrophotographic photoreceptor, which is driven to rotate around an axis 2 in the direction of the arrow at a predetermined peripheral speed. The surface of the electrophotographic photoreceptor 1 is charged to a predetermined positive or negative potential by a charging means 3. Although the figure shows a roller charging method using a roller-type charging member, a corona charging method, a proximity charging method, an injection charging method, or other charging methods may be adopted. The charged surface of the electrophotographic photoreceptor 1 is irradiated with image exposure light 4 from an exposure means (not shown), and an electrostatic latent image corresponding to the target image information is formed. The electrostatic latent image formed on the surface of the electrophotographic photoreceptor 1 is developed with toner contained in a developing means 5, and a toner image is formed on the surface of the electrophotographic photoreceptor 1. The toner image formed on the surface of the electrophotographic photoreceptor 1 is transferred to a transfer material 7 by a transfer means 6. The transfer material 7 to which the toner image has been transferred is transported to a fixing means 8, where the toner image is fixed, and the transfer material 7 is printed out from the electrophotographic device. The electrophotographic apparatus may have a cleaning means 9 for removing deposits such as toner remaining on the surface of the electrophotographic photoreceptor 1 after transfer. A so-called cleanerless system may be used in which the deposits are removed by a developing means or the like without providing a separate cleaning means. The electrophotographic apparatus may have a charge removing mechanism for removing charge from the surface of the electrophotographic photoreceptor 1 by pre-exposure light 10 from a pre-exposure means (not shown). A guide means 12 such as a rail may be provided to make the process cartridge of the present invention detachable from the main body of the electrophotographic apparatus.

[0062] The electrophotographic photoreceptor of the present invention can be used in laser beam printers, LED printers, copiers, facsimiles, and combination machines thereof.

[0063] [toner] The toner of the present embodiment includes toner particles containing a binder resin and inorganic fine particles. The inorganic fine particles can be present on the surface of the toner particles. The toner may further include a resin, a wax, a colorant, and the like.

[0064] Each of the components, such as the inorganic fine particles, the resin, the wax, and the colorant, will be described below. Also, components that can be contained in the toner, such as a magnetic material, a charge control agent, and a developer, and a method for producing the toner will be described.

[0065] <Inorganic fine particles> In the present invention, at least strontium titanate particles are used as the inorganic fine particles. The inorganic fine particles may be used alone or in combination of two or more kinds. When using in combination of two or more kinds, as long as at least one kind is a strontium titanate particle, inorganic fine particles other than the strontium titanate particle may be used. Examples of inorganic fine particles other than strontium titanate particles include alkaline earth metal titanate particles such as calcium titanate particles and magnesium titanate particles; and alkali metal titanate particles such as potassium titanate particles.

[0066] In the present invention, the strontium titanate particles preferably have a perovskite crystal structure. Strontium titanate particles having a perovskite crystal structure are produced mainly in an aqueous medium without going through a sintering process. For this reason, they are preferably used because they are easy to control to a uniform particle size.

[0067] The effect of the present invention can be obtained when the number average particle size of the primary particles of the strontium titanate particles is 20 nm or more and 70 nm or less. In addition, in the particle size distribution thereof, it is preferable that the peak top of the number frequency is within the above particle size range.

[0068] The inorganic fine particles are preferably hydrophobized on the surface by a surface treatment agent, such as fatty acid or a metal salt thereof, a disilylamine compound, a halogenated silane compound, silicone oil, a silane coupling agent, or a titanium coupling agent.

[0069] The toner particles and the inorganic fine particles can be mixed using a known mixer such as a Henschel mixer, Mechano Hybrid (manufactured by Nippon Coke Corporation), a Super Mixer, or Nobilta (manufactured by Hosokawa Micron Corporation), and is not particularly limited. The inorganic fine particles are mixed preferably in an amount of 0.05 to 2 parts by mass, more preferably 0.1 to 1.5 parts by mass, per 100 parts by mass of the toner particles.

[0070] Strontium titanate particles can be obtained, for example, by a normal pressure heating reaction method. In this case, it is preferable to use a mineral acid peptized product of a hydrolyzate of a titanium compound as the titanium oxide source, and a water-soluble acidic strontium compound as the strontium oxide source. The strontium titanate particles can be produced by reacting the mixture of these with an aqueous alkali solution at 60°C or higher, followed by acid treatment.

[0071] The atmospheric pressure heating reaction method and the acid treatment are described below. (Normal pressure heating reaction method) As a titanium oxide source for the strontium titanate particles, a mineral acid peptized product of a hydrolyzate of a titanium compound can be used. 3 Metatitanic acid having a content of 1.0 mass % or less, preferably 0.5 mass % or less, which has been peptized by adjusting the pH to 0.7 to 1.5 with hydrochloric acid, can be used. As the strontium oxide source, metal nitrates, hydrochlorides, etc., such as strontium nitrate and strontium chloride, can be used.

[0072] As the aqueous alkaline solution, a caustic alkali can be used, and among them, an aqueous sodium hydroxide solution is preferable.

[0073] In the method for producing strontium titanate particles, factors that affect the particle size include the mixing ratio of the titanium oxide source and the strontium oxide source during the reaction, the titanium oxide source concentration at the beginning of the reaction, and the temperature and addition rate when adding the alkaline aqueous solution. These can be appropriately adjusted to obtain the desired particle size and particle size distribution. In order to prevent the formation of carbonates during the reaction process, it is preferable to prevent the inclusion of carbon dioxide gas, for example by carrying out the reaction under a nitrogen gas atmosphere.

[0074] In the method for producing strontium titanate particles, factors that affect the dielectric constant of the resulting strontium titanate particles include conditions / operations that disrupt the crystallinity of the particles. In particular, in order to obtain strontium titanate particles with a low dielectric constant, it is preferable to carry out an operation that provides energy that disrupts crystal growth while increasing the concentration of the reaction solution. A specific example of such a method is to add microbubbles with nitrogen to the crystal growth process.

[0075] The mixing ratio of the titanium oxide source and the strontium oxide source during the reaction was SrO / TiO 2 The molar ratio is preferably 0.9 to 1.4, and more preferably 1.05 to 1.20. When the molar ratio is within the above range, unreacted titanium oxide is unlikely to remain. The concentration of the titanium oxide source at the beginning of the reaction is preferably TiO 2 The concentration is preferably 0.05 to 1.3 mol / L, and more preferably 0.08 to 1.0 mol / L.

[0076] The temperature when the alkaline aqueous solution is added is preferably 60°C to 100°C. The slower the addition rate of the alkaline aqueous solution, the larger the particle size of the strontium titanate particles obtained, and the faster the addition rate, the smaller the particle size of the strontium titanate particles obtained. The addition rate of the alkaline aqueous solution is preferably 0.001 to 1.2 equivalents / h, more preferably 0.002 to 1.1 equivalents / h, based on the charged raw material, and can be appropriately adjusted depending on the particle size to be obtained.

[0077] (Acid treatment) It is preferable that the strontium titanate particles obtained by the normal pressure heating reaction are further treated with an acid. When the normal pressure heating reaction is carried out to synthesize the strontium titanate particles, the mixture ratio of the titanium oxide source and the strontium oxide source is SrO / TiO 2 In terms of the molar ratio, if it exceeds 1.0, it may be undesirable. That is, the unreacted metal source other than titanium remaining after the reaction may react with carbon dioxide gas in the air to generate impurities such as metal carbonates. If impurities such as metal carbonates remain on the surface, the organic surface treatment agent cannot be uniformly coated due to the influence of the impurities when performing an organic surface treatment to impart hydrophobicity. Therefore, it is preferable to perform an acid treatment to remove the unreacted metal source after adding the alkaline aqueous solution. In the acid treatment, it is preferable to adjust the pH to 2.5 to 7.0, more preferably 4.5 to 6.0, using hydrochloric acid. As the acid, other than hydrochloric acid, such as nitric acid and acetic acid can be used for the acid treatment.

[0078] <Other external additives> In addition to the inorganic fine particles described above, the toner may contain other inorganic fine powders as necessary to adjust the charge amount and fluidity. The inorganic fine powders may be added internally or externally to the toner particles. As the external additive, inorganic fine powders such as silica, titanium oxide, aluminum oxide, magnesium oxide, and calcium carbonate are preferred. The inorganic fine powders are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof. The specific surface area of ​​the external additive used is 10 m 2 / g or more 50m 2 / g or less of inorganic fine particles is preferable from the viewpoint of suppressing embedding of external additives. The external additive is preferably used in an amount of 0.1 parts by mass or more and 5.0 parts by mass or less with respect to 100 parts by mass of the toner particles. The toner particles and the external additives can be mixed using a known mixer such as a Henschel mixer, but the device is not particularly limited as long as it can mix them.

[0079] <Resin> The binder resin used in the toner particles of the present invention is not particularly limited, and the following polymers or resins can be used. For example, homopolymers of styrene and its substitutes such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene-p-chlorostyrene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-acrylic acid ester copolymers, styrene-methacrylic acid ester copolymers, styrene-α-chloromethyl methacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, and styrene-acrylonitrile-indene copolymers; polyvinyl chloride, phenolic resins, naturally modified phenolic resins, naturally modified maleic acid resins, acrylic resins, methacrylic resins, polyvinyl acetate, silicone resins, polyester resins, polyurethanes, polyamide resins, furan resins, epoxy resins, xylene resins, polyvinyl butyral, terpene resins, coumarone-indene resins, and petroleum-based resins can be used.

[0080] Of these, it is preferable to use polyester resins from the viewpoint of improving cleaning properties. The polyester resin is preferably a resin having a "polyester unit" in the binder resin chain. Specific examples of components constituting the polyester unit include the following: Divalent or higher alcohol monomer components, divalent or higher carboxylic acids, divalent or higher carboxylic anhydrides, divalent or higher carboxylic acid esters, and the like.

[0081] Examples of the dihydric or higher alcohol monomer component include alkylene oxide adducts of bisphenol A such as polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, and polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane; ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-propylene glycol, 1,5-propylene glycol, 1,6-propylene glycol, 1,7-propylene glycol, 1,8-propylene glycol, 1,9-propylene glycol, 2,10-propylene glycol, 2,11-propylene glycol, 2,22-propylene glycol, 2,3-propylene glycol, 2,4-propylene glycol, 2,5-propylene glycol, 2,6-propylene glycol, 2,7-propylene glycol, 2,8-propylene glycol, 2,9-propylene glycol, 2,11-propylene glycol, 2,12-propylene glycol, 2,13-propylene glycol, 2,14-propylene glycol, 2,15-propylene glycol, 2,16-propylene glycol, 2,17-propylene glycol, 2,18-propylene glycol, 2,19-propylene glycol, 2,22-propylene glycol, 2,23-propylene glycol, 2,24-propylene glycol, 2,25-propylene glycol, 2,26-propylene glycol, 2,27-propylene glycol, 2,28-propylene glycol, 2,29-propylene glycol, 2,30-propylene glycol, 2,31-propylene glycol, 2,32-propylene glycol, 2,33-propylene glycol, 2,34-propylene glycol, 2,35- ,4-butanediol, neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerin, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, 1,3,5-trihydroxymethylbenzene, and the like. Among these, the alcohol monomer component that is preferably used is an aromatic diol, and the alcohol monomer component that constitutes the polyester resin preferably contains the aromatic diol in a proportion of 80 mol % or more.

[0082] On the other hand, examples of the acid monomer components such as the divalent or higher carboxylic acid, the divalent or higher carboxylic acid anhydride, and the divalent or higher carboxylic acid ester include the following: aromatic dicarboxylic acids or anhydrides thereof such as phthalic acid, isophthalic acid, and terephthalic acid, alkyl dicarboxylic acids or anhydrides thereof such as succinic acid, adipic acid, sebacic acid, and azelaic acid, succinic acid or anhydrides thereof substituted with an alkyl or alkenyl group having 6 to 18 carbon atoms, and unsaturated dicarboxylic acids or anhydrides thereof such as fumaric acid, maleic acid, and citraconic acid. Among these, preferred acid monomer components are polyvalent carboxylic acids such as terephthalic acid, succinic acid, adipic acid, fumaric acid, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and anhydrides thereof.

[0083] In addition, the acid value of the polyester resin is preferably 20 mgKOH / g or less from the viewpoint of improving cleaning properties. More preferably, it is 15 mgKOH / g or less. If the acid value exceeds 20 mgKOH / g, the toner has uneven moisture absorption properties, which deteriorates the fluidity and affects the cleaning properties. The acid value can be adjusted to the above range by adjusting the type and amount of monomers used in the resin. Specifically, the acid value can be controlled by adjusting the alcohol monomer component ratio / acid monomer component ratio and molecular weight during resin production. In addition, the acid value can be controlled by reacting the terminal alcohol with a polyacid monomer (e.g., trimellitic acid) after ester condensation polymerization.

[0084] [Crystalline polyester resin] The toner of the present invention may also contain a crystalline polyester resin. From the viewpoint of improving cleaning properties, the content of the crystalline polyester resin is preferably 5.0 parts by mass or more and 30.0 parts by mass or less, and more preferably 10.0 parts by mass or more and 20.0 parts by mass or less, relative to 100.0 parts by mass of the binder resin. In the present invention, a crystalline resin is a resin in which an endothermic peak is observed in differential scanning calorimetry (DSC). The crystalline polyester resin can be obtained by the reaction of a divalent or higher polyvalent carboxylic acid and a diol. Among them, a resin obtained by polycondensation of an aliphatic diol and an aliphatic dicarboxylic acid is preferable. In the present invention, the crystalline polyester resin may be used alone or in combination of two or more kinds.

[0085] In the present invention, the crystalline polyester resin is preferably a resin obtained by condensation polymerization of the following alcohol component and carboxylic acid component. That is, the alcohol component is preferably an alcohol component containing at least one compound selected from the group consisting of aliphatic diols having 2 to 22 carbon atoms and their derivatives. The carboxylic acid component is preferably a carboxylic acid component containing at least one compound selected from the group consisting of aliphatic dicarboxylic acids having 2 to 22 carbon atoms and their derivatives.

[0086] Among them, the crystalline polyester resin is preferably a resin obtained by condensing the following alcohol component and carboxylic acid component from the viewpoint of improving cleaning properties. That is, the alcohol component is preferably an alcohol component containing at least one compound selected from the group consisting of aliphatic diols having 6 to 12 carbon atoms and their derivatives. The carboxylic acid component is preferably a carboxylic acid component containing at least one compound selected from the group consisting of aliphatic dicarboxylic acids having 6 to 12 carbon atoms and their derivatives.

[0087] The aliphatic diol having 2 to 22 carbon atoms (preferably having 6 to 12 carbon atoms) is not particularly limited, but is most preferably a chain (preferably linear) aliphatic diol from the viewpoint of improving cleaning properties. Examples include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, dipropylene glycol, 1,3-propanediol, 1,4-butanediol, 1,4-butadiene glycol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol. Among these, preferred examples include straight-chain aliphatic α,ω-diols such as 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol.

[0088] In the present invention, the derivative of the aliphatic diol is not particularly limited as long as it can be obtained by condensation polymerization with a resin structure similar to that of the aliphatic diol exemplified above. For example, the derivative of the above diol is esterified.

[0089] In the present invention, the alcohol component constituting the crystalline polyester resin is preferably as follows: That is, at least one compound selected from the group consisting of the aliphatic diols having 2 to 22 carbon atoms (preferably 6 to 12 carbon atoms) and their derivatives is preferably 50% by mass or more, and more preferably 70% by mass or more, based on the total alcohol component.

[0090] In the present invention, polyhydric alcohols other than the above aliphatic diols can also be used. Among the polyhydric alcohols, examples of diols other than the above-mentioned aliphatic diols include aromatic alcohols such as polyoxyethylenated bisphenol A and polyoxypropylenated bisphenol A; 1,4-cyclohexanedimethanol, and the like. Furthermore, examples of the trivalent or higher polyhydric alcohols among the polyhydric alcohols include aromatic alcohols such as 1,3,5-trihydroxymethylbenzene; and aliphatic alcohols such as pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerin, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, and trimethylolpropane.

[0091] Furthermore, in the present invention, monohydric alcohols may be used to the extent that they do not impair the properties of the crystalline polyester resin. Examples of the monohydric alcohols include n-butanol, isobutanol, sec-butanol, n-hexanol, n-octanol, 2-ethylhexanol, cyclohexanol, and benzyl alcohol.

[0092] On the other hand, the aliphatic dicarboxylic acid having 2 to 22 carbon atoms (preferably 6 to 12 carbon atoms) is not particularly limited, but may be a chain (preferably linear) aliphatic dicarboxylic acid. Examples include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, glutaconic acid, azelaic acid, sebacic acid, nonanedicarboxylic acid, decanedicarboxylic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, maleic acid, fumaric acid, mesaconic acid, citraconic acid, and itaconic acid. Also included are those obtained by hydrolyzing the acid anhydrides or lower alkyl esters of these.

[0093] In the present invention, the derivative of the aliphatic dicarboxylic acid is not particularly limited as long as it can be obtained by condensation polymerization with a similar resin structure to the above-listed aliphatic carboxylic acids. For example, the derivative may be an acid anhydride of the above dicarboxylic acid component, or a derivative obtained by methyl esterification, ethyl esterification, or acid chloride of the dicarboxylic acid component.

[0094] In the present invention, the ratio of aliphatic dicarboxylic acids or derivatives thereof to all carboxylic acid components constituting the crystalline polyester resin is preferably as follows: That is, at least one compound selected from the group consisting of the aliphatic dicarboxylic acids having 2 to 22 carbon atoms (preferably 6 to 12 carbon atoms) and their derivatives is preferably 50% by mass or more, and more preferably 70% by mass or more, based on all carboxylic acid components.

[0095] In the present invention, polyvalent carboxylic acids other than the above-mentioned aliphatic dicarboxylic acids can also be used. Among the polyvalent carboxylic acids, examples of divalent carboxylic acids other than the above-mentioned aliphatic dicarboxylic acids include aromatic carboxylic acids such as isophthalic acid and terephthalic acid, aliphatic carboxylic acids such as n-dodecyl succinic acid and n-dodecenyl succinic acid, and alicyclic carboxylic acids such as cyclohexane dicarboxylic acid, and also include their acid anhydrides or lower alkyl esters.

[0096] Furthermore, among other polyvalent carboxylic acids, examples of trivalent or higher polyvalent carboxylic acids include aromatic carboxylic acids such as 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, and pyromellitic acid, and aliphatic carboxylic acids such as 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, and 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, as well as derivatives such as acid anhydrides and lower alkyl esters of these.

[0097] Furthermore, in the present invention, monovalent carboxylic acids may be used to the extent that they do not impair the properties of the crystalline polyester resin. Examples of the monovalent carboxylic acids include benzoic acid, naphthalene carboxylic acid, salicylic acid, 4-methylbenzoic acid, 3-methylbenzoic acid, phenoxyacetic acid, biphenyl carboxylic acid, acetic acid, propionic acid, butyric acid, and octanoic acid.

[0098] In the present invention, the crystalline polyester resin can be produced according to a conventional polyester synthesis method. For example, the crystalline polyester resin can be obtained by esterifying or transesterifying the carboxylic acid component and the alcohol component, and then condensing the mixture under reduced pressure or by introducing nitrogen gas according to a conventional method. The above esterification or transesterification reaction can be carried out, if necessary, using a common esterification catalyst or transesterification catalyst such as sulfuric acid, titanium butoxide, tin 2-ethylhexanoate, dibutyltin oxide, manganese acetate, or magnesium acetate.

[0099] The condensation polymerization reaction can be carried out using a conventional polymerization catalyst, such as titanium butoxide, tin 2-ethylhexanoate, dibutyltin oxide, tin acetate, zinc acetate, tin disulfide, antimony trioxide, germanium dioxide, etc. The polymerization temperature and the amount of catalyst are not particularly limited and may be appropriately determined.

[0100] In the esterification or transesterification reaction, or polycondensation reaction, the following methods can be used to increase the strength of the resulting crystalline polyester resin: All monomers may be charged at once, or a divalent monomer may be reacted first to reduce low molecular weight components, and then a trivalent or higher monomer may be added and reacted.

[0101] <Wax> The toner of the present invention may contain a wax if necessary. Examples of waxes include the following: hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; waxes containing fatty acid esters as the main component such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax. In addition, the following may be mentioned. Saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and valinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene bis Saturated fatty acid bisamides such as stearic acid amide; unsaturated fatty acid amides such as ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, and N,N'-dioleyl sebacic acid amide; aromatic bisamides such as m-xylene bisstearic acid amide and N,N'-distearyl isophthalic acid amide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxyl groups obtained by hydrogenating vegetable oils and fats. Among these waxes, Fischer-Tropsch wax is preferred from the viewpoint of controlling fluidity and improving cleaning properties.

[0102] The wax is preferably used in an amount of 0.5 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the binder resin. More preferably, the wax is used in an amount of 3.0 parts by mass or more and 12 parts by mass or less. From the viewpoint of improving the cleaning properties of the toner, the wax preferably has a maximum endothermic peak temperature in the temperature range of 30° C. to 200° C. of less than 50° C. and 110° C. of less than 50° C., and even more preferably has a peak temperature of 70° C. to 100° C. The peak temperature can be shown in an endothermic curve during temperature rise measured by a differential scanning calorimeter (DSC).

[0103] <Coloring agent> Examples of colorants (coloring materials) that can be contained in the toner of the present invention include the following.

[0104] Examples of black colorants include carbon black, yellow colorants, magenta colorants, and cyan colorants used to tone the color to black. As the colorant, a pigment may be used alone, but it is more preferable to use a dye and a pigment in combination to improve the clarity of the colorant from the viewpoint of the image quality of a full-color image.

[0105] Magenta colored pigments include: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35. Magenta coloring dyes include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and basic dyes such as CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.

[0106] Cyan coloring pigments include the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45, copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton. Cyan coloring dyes include CI Solvent Blue 70.

[0107] Yellow coloring pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow coloring dyes include CI Solvent Yellow 162.

[0108] The content of the colorant is preferably 0.1 parts by mass or more and 30.0 parts by mass or less with respect to 100 parts by mass of the binder resin.

[0109] <Magnetic material> The toner of the present invention may be a magnetic toner or a non-magnetic toner. When used as a magnetic toner, it is preferable to use magnetic iron oxide as the magnetic material. As the magnetic iron oxide, iron oxide such as magnetite, maghematite, and ferrite is used. The amount of magnetic iron oxide added to the toner is preferably 25 parts by mass or more and 95 parts by mass or less, more preferably 30 parts by mass or more and 45 parts by mass or less, based on 100 parts by mass of the binder resin.

[0110] <Charge control agent> The toner of the present invention may contain a charge control agent as necessary. Known charge control agents may be used as the charge control agent contained in the toner, but metal compounds of aromatic carboxylic acids are particularly preferred because they are colorless, can charge the toner quickly, and can stably maintain a constant charge amount. Examples of negative charge control agents include the following: metal salicylate compounds, metal naphthoate compounds, and metal dicarboxylate compounds. Further examples include polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, and polymeric compounds having carboxylate or carboxylate ester on the side chain. Further examples include boron compounds, urea compounds, silicon compounds, and calixarenes. The charge control agent may be added internally or externally to the toner particles. The amount of the charge control agent added is preferably 0.2 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the binder resin.

[0111] <Developer> The toner of the present invention can be used as a one-component developer, but in order to further improve dot reproducibility, it is preferable to mix it with a magnetic carrier and use it as a two-component developer. It is also preferable in that stable images can be obtained over a long period of time. Examples of magnetic carriers that can be used include generally known magnetic carriers such as surface-oxidized iron powder, unoxidized iron powder, metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, chromium, and rare earth elements, alloy particles thereof, oxide particles, magnetic materials such as ferrite, and magnetic material-dispersed resin carriers (so-called resin carriers) that contain a magnetic material and a binder resin that holds the magnetic material in a dispersed state.

[0112] In the present invention, when the toner is mixed with a magnetic carrier to be used as a two-component developer, the mixing ratio is preferably such that the toner concentration in the two-component developer is 2% by mass or more and 15% by mass or less, and more preferably 4% by mass or more and 13% by mass or less.

[0113] (Method of manufacturing toner particles) The toner particles can be produced by any known method, such as a wet production method or a kneading and pulverizing method. Below, toner manufacturing procedures using [1] the wet manufacturing method (emulsion aggregation method) and [2] the kneading and grinding method will be described as examples.

[0114] [1] Wet manufacturing method (emulsification aggregation method) In the emulsion aggregation method, first, a dispersion liquid of each material such as binder resin particles and colorant is prepared. The obtained dispersion liquid of each material is dispersed and mixed by adding a dispersion stabilizer as necessary. Then, an aggregating agent is added to aggregate the particles to the desired toner particle size, and then or simultaneously with the aggregation, the resin particles are fused together. If necessary, the shape is controlled by heat to form toner particles. Here, the binder resin particles can be composite particles formed of two or more layers made of resins with different compositions. For example, they can be produced by emulsion polymerization, mini-emulsion polymerization, phase inversion emulsification, or the like, or by combining several production methods.

[0115] When the internal additive is contained in the toner particles, the internal additive may be contained in the resin fine particles, or a dispersion liquid of internal additive fine particles consisting of only the internal additive may be separately prepared and the internal additive fine particles may be aggregated together with the resin fine particles when the internal additive fine particles are aggregated. Also, by adding resin fine particles having different compositions at different times during aggregation and aggregating them, toner particles having layer structures with different compositions can be produced.

[0116] The following can be used as the dispersion stabilizer. As the surfactant, a known cationic surfactant, anionic surfactant, or nonionic surfactant can be used. Examples of inorganic dispersion stabilizers include tricalcium phosphate, magnesium phosphate, zinc phosphate, aluminum phosphate, calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, bentonite, silica, and alumina. Examples of the organic dispersion stabilizer include polyvinyl alcohol, gelatin, methyl cellulose, methylhydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, and starch.

[0117] From the viewpoint of high definition and high resolution of images, it is preferable that the weight average particle size of the toner particles is 3.0 μm or more and 10.0 μm or less.

[0118] [2] Kneading and grinding method In the raw material mixing process, materials constituting the toner particles, such as polyester resin, fatty acid metal salt, aluminum pigment, and other components such as a release agent and a charge control agent as necessary, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include a double con mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, and a Mechano Hybrid (manufactured by Nippon Coke and Engineering Co., Ltd.).

[0119] Next, the mixed materials are melt-kneaded. In the melt-kneading step, a batch type kneader such as a pressure kneader or a Banbury mixer, or a continuous type kneader can be used, and a single-screw or twin-screw extruder is preferred because of its advantage of being capable of continuous production. The temperature for melt-kneading is preferably about 100 to 200°C. Examples of such extruders include a KTK type twin screw extruder (manufactured by Kobe Steel, Ltd.), a TEM type twin screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), a twin screw extruder (manufactured by KCK Corporation), a Co-Kneader (manufactured by Buss Co., Ltd.), and a Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) Furthermore, the resin composition obtained by melt kneading is rolled with two rolls or the like, and quenched with water or the like in a cooling process.

[0120] The cooled resin composition is then pulverized to a desired particle size in a pulverization process. In the pulverization process, the resin composition is coarsely pulverized using a pulverizer such as a crusher, a hammer mill, or a feather mill. The resin composition is then finely pulverized using a pulverizer such as a Cryptron System (Kawasaki Heavy Industries), a Super Rotor (Nisshin Engineering), a Turbo Mill (Turbo Kogyo), or an air jet type pulverizer.

[0121] Thereafter, if necessary, the mixture is classified using a classifier or a sieve to obtain classified products (toner particles). Examples of classifiers and sieves include the following: Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), which uses an inertial classification method, and Turboplex (manufactured by Hosokawa Micron Corporation), TSP Separator (manufactured by Hosokawa Micron Corporation), and Faculty (manufactured by Hosokawa Micron Corporation), which uses a centrifugal classification method.

[0122] Examples of the method for externally adding an external additive to the surface of the obtained toner particles include the following. That is, a method in which a predetermined amount of a known external additive is mixed with the toner particles and stirred and mixed using a mixer as an external adder is exemplified. Examples of the mixer include the following. That is, a double con mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke and Engineering Co., Ltd.), and a Nobilta (manufactured by Hosokawa Micron Corporation) are exemplified.

[0123] The toner of the present invention preferably has a volume-based median diameter of 3.0 μm or more and 10.0 μm or less. EXAMPLES

[0124] The present invention will be described in more detail below using examples and comparative examples. The present invention is not limited to the following examples without departing from the gist of the present invention. In the following examples, "parts" are by mass unless otherwise specified.

[0125] Example 1 <Preparation of Electrophotographic Photoreceptor> The support was an aluminum cylinder with a diameter of 30.5 mm, a length of 370 mm, and a wall thickness of 1 mm.

[0126] [Undercoat layer] Zinc oxide particles (average particle size: 70 nm, specific surface area: 15 m 2 60 parts of ZnO (100% NaOH / g) were mixed with 500 parts of tetrahydrofuran and stirred. 0.75 parts of a silane coupling agent were added thereto and stirred for 2 hours. As the silane coupling agent, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (product name: KBM603, manufactured by Shin-Etsu Chemical Co., Ltd.) was used. Thereafter, tetrahydrofuran was distilled off under reduced pressure, and the mixture was dried by heating at 120°C for 3 hours to obtain surface-treated zinc oxide particles. Next, 25 parts of butyral (product name: BM-1, manufactured by Sekisui Chemical Co., Ltd.) as a polyol and 22.5 parts of blocked isocyanate (product name: Sumidur BL-3173, manufactured by Sumitomo Bayern Urethane Co., Ltd.) were dissolved in 142 parts of methyl ethyl ketone. 100 parts of the surface-treated zinc oxide particles and 1 part of anthraquinone were added to this solution, and the mixture was dispersed in a sand mill using glass beads with a diameter of 1 mm for 5 hours. After the dispersion treatment, 0.008 parts of dioctyltin dilaurate and 6.5 parts of silicone resin particles (Tospearl 145, manufactured by GE Toshiba Silicones) were added and stirred to prepare a coating liquid for an undercoat layer. The obtained coating liquid for undercoat layer was dip-coated onto the support to form a coating film, and the coating film was dried at 190° C. for 24 minutes to form an undercoat layer with a thickness of 15 μm.

[0127] [Charge generation layer] The following was mixed: 15 pieces of hydroxygallium phthalocyanine crystals with strong peaks at 7.4° and 28.2° of Bragg angle 2θ±0.2° in CuKα characteristic X-ray diffraction Vinyl chloride-vinyl acetate copolymer resin (VMCH, manufactured by Nippon Union Carbide Co., Ltd.) 10 parts 300 parts n-butyl alcohol The resulting mixture was dispersed for 4 hours in a sand mill using glass beads with a diameter of 1 mm to prepare a coating liquid for the charge generating layer. This charge generating layer coating liquid was dip coated onto the undercoat layer, and the resulting coating was dried at 100° C. for 10 minutes to form a charge generating layer having a thickness of 0.2 μm.

[0128] [Charge transport layer] A coating solution for the charge transport layer was prepared as follows. 30 parts of a compound represented by the following formula (C): 60 parts of a compound represented by the following formula (D): 10 parts of a compound represented by the following formula (E): Polycarbonate resin (product name: Iupilon Z400, manufactured by Mitsubishi Engineering Plastics Co., Ltd., bisphenol Z type) 100 parts 0.02 parts of polycarbonate (viscosity average molecular weight Mv: 20,000) represented by the following formula (F) of, 270 parts mixed xylene 275 parts dimethoxymethane Methyl benzoate 250 parts The mixture was dissolved in a solvent consisting of This charge transport layer coating liquid was dip coated onto the charge generating layer to form a coating film, and the resulting coating film was dried at 100° C. for 30 minutes to form a charge transport layer with a thickness of 18 μm. [ka]

[0129] [Surface layer] Polytetrafluoroethylene particles (product name: Lubron L-2, manufactured by Daikin Industries, Ltd.) were subjected to particle size adjustment using an elbow jet classifier to obtain polytetrafluoroethylene particles having the particle size and abundance ratio shown in Table 1.

[0130] (Method for measuring the particle size of primary particles) Polytetrafluoroethylene particles were attached to a commercially available carbon conductive tape, and particles not attached to the conductive tape were removed with compressed air, followed by platinum deposition. The deposited particles were observed using a Hitachi High-Technologies Corporation FE-SEM (S-4700). The measurement conditions for the FE-SEM were set as follows: Acceleration voltage: 2 kV WD: 5mm Magnification: 20,000 times Number of pixels: 1280 pixels vertically, 960 pixels horizontally (size of one pixel: 5 nm) From the obtained images, the Feret's diameter of 500 particles was determined using ImageJ (open source software from the National Institutes of Health (NIH)), and the average primary particle diameter and abundance ratio of polytetrafluoroethylene particles were calculated.

[0131] 6.1 parts of polytetrafluoroethylene particles No. 1 in Table 1, 0.20 parts of copolymer resin, and 15 parts of cyclopentanone were stirred and mixed. This was passed through a high-pressure disperser (product name: Microfluidizer M-110EH, manufactured by Microfluidics, Inc., USA) to obtain a dispersion. However, the copolymer resin used had a repeating structural unit represented by the following formula (G) and a repeating structural unit represented by the following formula (H), a weight average molecular weight of 130,000, and a copolymerization ratio (G) / (H)=1 / 1 (molar ratio). Next, 18 parts of the charge transporting compound represented by formula (2-10), 1 part of the melamine compound represented by the following formula (I), 10 parts of cyclopentanone, and 0.04 parts of NCURE5225 (King Industries) were mixed and dissolved to obtain a mixed solution. The dispersion was added to this mixture, stirred and mixed, and then filtered through a polytetrafluoroethylene filter (product name: PF-040, manufactured by Advantec Toyo Co., Ltd.) to prepare a coating liquid for the surface layer. This coating liquid was dip-coated onto the charge transport layer, and the resulting coating film was heat-treated at 150° C. for 60 minutes to form a surface layer with a film thickness of 5 μm. [ka] [ka]

[0132] [Table 1]

[0133] (Production of Strontium Titanate No.1) The titanium oxide hydrous slurry obtained by hydrolysis of the titanyl sulfate aqueous solution was washed with an alkaline aqueous solution until the electrical conductivity of the supernatant liquid reached 50 μS / cm, reducing impurities and purifying it. Next, hydrochloric acid was added to the titanium oxide hydrous slurry to adjust the pH to 0.7 to obtain a titania sol dispersion. A strontium chloride aqueous solution was added in an amount of 1.2 times the molar amount per 2.0 moles (titanium oxide equivalent) of the titania sol dispersion, and the mixture was placed in a reaction vessel and substituted with nitrogen gas. Furthermore, pure water was added to the titanium oxide concentration of 1.0 mole / L. Next, the mixture was stirred and heated to 85°C, and then 800mL of 5N sodium hydroxide solution was added over 20 minutes while applying ultrasonic vibration, and the reaction was then carried out for 20 minutes. After the reaction, pure water at 5°C was added to the slurry, which was then rapidly cooled to 30°C or less, and the supernatant liquid was removed. Furthermore, a hydrochloric acid solution at pH 5.0 was added to the slurry, which was stirred for 1 hour to dissolve and remove strontium carbonate, and the mixture was repeatedly washed with pure water. Next, a hydrochloric acid solution of pH 3.0 was added to the slurry, and then 30.0 mass% of isobutyltrimethoxysilane was added to the solid content of the slurry and stirred for 10 hours. Then, the slurry was neutralized with a sodium hydroxide solution, filtered through a Nutsche filter, and washed with pure water. The resulting cake was dried to obtain strontium titanate No. 1. The number average particle size (nm) of the primary particles of strontium titanate is shown in Table 2.

[0134] (Production of Strontium Titanate No. 2) The titanium oxide hydrous slurry obtained by hydrolysis of the titanyl sulfate aqueous solution was washed with an alkaline aqueous solution until the electrical conductivity of the supernatant liquid reached 100 μS / cm, reducing impurities and purifying it. Next, hydrochloric acid was added to the titanium oxide hydrous slurry to adjust the pH to 0.7 to obtain a titania sol dispersion. A strontium chloride aqueous solution of 1.1 times the molar amount was added to 1.4 moles (titanium oxide equivalent) of the titania sol dispersion, which was then placed in a reaction vessel and substituted with nitrogen gas. Furthermore, pure water was added to the titanium oxide concentration of 0.7 moles / L. Next, the mixture was stirred and heated to 80°C, and then 1000mL of 3N sodium hydroxide solution was added over 40 minutes while applying ultrasonic vibration, and the reaction was then carried out for 20 minutes. The slurry after the reaction was gradually cooled to 30°C or less over 1 hour, and the supernatant liquid was removed. Furthermore, a hydrochloric acid solution of pH 5.0 was added to the slurry and stirred for 1 hour to dissolve and remove strontium carbonate, and then the mixture was repeatedly washed with pure water. Next, a hydrochloric acid solution of pH 3.0 was added to the slurry, and then 2.0 mass% of n-octyltriethoxysilane was added to the solid content of the slurry and stirred for 10 hours. Then, the slurry was neutralized with a sodium hydroxide solution, filtered through a Nutsche filter, and washed with pure water. The resulting cake was dried to obtain strontium titanate No. 2. The number average particle size (nm) of the primary particles of strontium titanate is shown in Table 2.

[0135] (Production of Strontium Titanate No.3) The titanium oxide hydrous slurry obtained by hydrolysis of the titanyl sulfate aqueous solution was washed with an alkaline aqueous solution until the electrical conductivity of the supernatant liquid reached 50 μS / cm to reduce impurities and purify the slurry. Next, hydrochloric acid was added to the titanium oxide hydrous slurry to adjust the pH to 0.7, thereby obtaining a titania sol dispersion. A strontium chloride aqueous solution having a molar amount of 1.2 times the amount of the titania sol dispersion (2.5 moles, calculated as titanium oxide) was added to a reaction vessel, which was then purged with nitrogen gas. Pure water was then added to the vessel so that the titanium oxide concentration became 0.9 moles / L. Next, the mixture was stirred and heated to 95°C, and then 312 mL of 15N sodium hydroxide solution was added over 5 minutes while applying ultrasonic vibration, and the reaction was then carried out for 20 minutes. After the reaction, pure water at 5°C was added to the slurry, which was then rapidly cooled to 30°C or less, and the supernatant liquid was removed. Furthermore, a hydrochloric acid solution at pH 5.0 was added to the slurry, which was stirred for 1 hour to dissolve and remove strontium carbonate, and the mixture was repeatedly washed with pure water. Next, a hydrochloric acid solution of pH 3.0 was added to the slurry, and then 7.0 mass% of n-octyltriethoxysilane was added to the solid content of the slurry and stirred for 10 hours. Then, the slurry was neutralized with a sodium hydroxide solution, filtered through a Nutsche filter, and washed with pure water. The resulting cake was dried to obtain strontium titanate No. 3. The number average particle size (nm) of the primary particles of strontium titanate is shown in Table 2.

[0136] (Production of Strontium Titanate No. 4) The titanium oxide hydrous slurry obtained by hydrolysis of the titanyl sulfate aqueous solution was washed with an alkaline aqueous solution until the electrical conductivity of the supernatant liquid reached 50 μS / cm to reduce impurities and purify the slurry. Next, hydrochloric acid was added to the titanium oxide hydrous slurry to adjust the pH to 0.7, thereby obtaining a titania sol dispersion. A strontium chloride aqueous solution having a molar amount of 1.2 times the amount of the titania sol dispersion (2.6 moles, calculated as titanium oxide) was added to a reaction vessel, which was then purged with nitrogen gas. Pure water was then added to the vessel so that the titanium oxide concentration became 1.3 moles / L. Next, the mixture was stirred and heated to 95°C, and then 312 mL of 15N sodium hydroxide solution was added over 5 minutes while applying ultrasonic vibration, and the reaction was then carried out for 20 minutes. After the reaction, pure water at 5°C was added to the slurry, which was then rapidly cooled to 30°C or less, and the supernatant liquid was removed. Furthermore, a hydrochloric acid solution at pH 5.0 was added to the slurry, which was stirred for 1 hour to dissolve and remove strontium carbonate, and the mixture was repeatedly washed with pure water. Next, a hydrochloric acid solution of pH 3.0 was added to the slurry, and then 5.0 mass% of isobutyltrimethoxysilane was added to the solid content of the slurry and stirred for 10 hours. Then, the slurry was neutralized with a sodium hydroxide solution, filtered through a Nutsche filter, and washed with pure water. The resulting cake was dried to obtain strontium titanate No. 4. The number average particle size (nm) of the primary particles of strontium titanate is shown in Table 2.

[0137] (Production of Strontium Titanate No.5) The titanium oxide hydrous slurry obtained by hydrolysis of the titanyl sulfate aqueous solution was washed with an alkaline aqueous solution until the electrical conductivity of the supernatant liquid reached 100 μS / cm to reduce impurities and purify the slurry. Next, hydrochloric acid was added to the titanium oxide hydrous slurry to adjust the pH to 0.7, thereby obtaining a titania sol dispersion. A strontium chloride aqueous solution having a molar amount of 1.1 times the amount of the titania sol dispersion (1.0 mole (equivalent to titanium oxide)) was added to a reaction vessel, which was then purged with nitrogen gas. Pure water was then added to the vessel so that the titanium oxide concentration became 0.5 mole / L. Next, the mixture was stirred and heated to 70°C, and then 1100mL of 2N sodium hydroxide solution was added over 40 minutes while applying ultrasonic vibration, and the reaction was then carried out for 20 minutes. The slurry after the reaction was gradually cooled to 30°C or less over 1 hour, and the supernatant liquid was removed. Furthermore, a hydrochloric acid solution of pH 5.0 was added to the slurry and stirred for 1 hour to dissolve and remove strontium carbonate, and then the mixture was repeatedly washed with pure water. Next, a hydrochloric acid solution of pH 3.0 was added to the slurry, and then 2.0 mass% of n-octyltriethoxysilane was added to the solid content of the slurry and stirred for 10 hours. Then, the slurry was neutralized with a sodium hydroxide solution, filtered through a Nutsche filter, and washed with pure water. The resulting cake was dried to obtain strontium titanate No. 5. The number average particle size (nm) of the primary particles of strontium titanate is shown in Table 2.

[0138] <Measurement of the number-average particle size of primary particles of strontium titanate> The number-average particle diameter of the primary particles of strontium titanate was determined by observing with a transmission electron microscope "H-800" (manufactured by Hitachi, Ltd.) and measuring the long axis of 100 primary particles in a field of view magnified up to 2 million times.

[0139] [Table 2]

[0140] <Production of polyester resin> In a reactor equipped with a stirrer, a thermometer, and an outflow cooler, 47 mol parts of terephthalic acid, 3 mol parts of isophthalic acid, 26 mol parts of ethylene oxide-modified bisphenol A (2-mol adduct), 18 mol parts of ethylene glycol, and 1000 ppm of tetrabutoxytitanium were placed and subjected to an esterification reaction at 190° C. Then, 6 mol parts of trimellitic anhydride (TMA) were added, and the temperature was raised to 220° C. while the pressure in the system was gradually reduced, and a polycondensation reaction was performed at 150 Pa to obtain a polyester resin.

[0141] <Preparation of Resin Particle Dispersion> 100.0 parts of polyester resin and 350 parts of ion-exchanged water were placed in a stainless steel container, heated to 95°C in a warm bath, and melted. While thoroughly stirring at 7,800 rpm using a homogenizer (IKA Ultra Turrax T50), 0.1 mol / L sodium bicarbonate was added to adjust the pH to greater than 7.0. Thereafter, a mixed solution of 3 parts of sodium dodecylbenzenesulfonate and 300 parts of ion-exchanged water was gradually added dropwise to emulsify and disperse the mixture, thereby obtaining a polyester resin particle dispersion. The dispersion was cooled to room temperature, and ion-exchanged water was added to obtain a resin particle dispersion having a solid content of 12.5% ​​by mass and a volume-based median diameter of 0.2 μm.

[0142] <Preparation of wax dispersion> 100 parts of hydrocarbon wax (melting point: 77°C) and 15 parts of NEOGEN RK were mixed with 385 parts of ion-exchanged water, and dispersed for about 1 hour using a wet jet mill JN100 (manufactured by Jokou Co., Ltd.) to obtain a wax dispersion. The concentration of the wax dispersion was 20% by mass.

[0143] <Preparation of Colorant Dispersion> As colorants, CI Pigment Blue 15:3 (100 parts) and 15 parts of NEOGEN RK were mixed with 885 parts of ion-exchanged water, and dispersed for about 1 hour using a wet jet mill JN100 to obtain a colorant dispersion.

[0144] <Preparation of toner particles> 265 parts of resin particle dispersion, 20 parts of wax dispersion, and 20 parts of colorant dispersion were dispersed using a homogenizer (IKA Ultra Turrax T50). The temperature inside the container was adjusted to 30°C while stirring, and a 1 mol / L aqueous sodium hydroxide solution was added to adjust the pH to 8.0 (pH adjustment 1). As a flocculant, an aqueous solution of 0.23 parts of aluminum chloride dissolved in 10 parts of ion-exchanged water was added over 10 minutes at 30°C while stirring. After leaving it for 3 minutes, the temperature was raised to 50°C to generate associated particles. In this state, the particle size of the associated particles was measured using a Coulter Counter Multisizer 3 (registered trademark, manufactured by Beckman Coulter, Inc.). When the weight average particle size reached 6.0 μm, 0.9 parts of sodium chloride and 5.0 parts of Neogen RK were added to stop particle growth. After adjusting the pH to 9.0 by adding 1 mol / L aqueous sodium hydroxide solution, the temperature was raised to 95° C. to spheroidize the aggregated particles. When the average circularity reached 0.980, the temperature was lowered and the mixture was cooled to room temperature to obtain a toner particle dispersion. Hydrochloric acid was added to the obtained toner particle dispersion to adjust the pH to 1.5 or less, and the mixture was left to stir for 1 hour, after which it was subjected to solid-liquid separation using a pressure filter to obtain a toner cake. This was reslurried with ion-exchanged water to make a dispersion again, and then the solid-liquid separation was performed using the above-mentioned filter. The reslurry and solid-liquid separation were repeated until the electrical conductivity of the filtrate was 5.0 μS / cm or less, and finally solid-liquid separation was performed to obtain a toner cake. The obtained toner cake was dried and further classified using a classifier so that the weight average particle size was 6.0 μm, to obtain toner particles.

[0145] <Toner manufacturing> To the obtained toner particles (100.0 parts), strontium titanate particles (1.0 part) of No. 1 in Table 2 and hydrophobic silica fine particles (1.0 part) having a primary particle number average particle diameter of 120 nm and surface-treated with 20.0 mass % of hexamethyldisilazane were added. The obtained additives were mixed in a Henschel mixer (FM75J type, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) at a rotation speed of 30 s. -1 The mixture was mixed at 100° C. for 5 minutes and passed through an ultrasonic vibration sieve with a mesh size of 54 μm to obtain a toner.

[0146] <Production of magnetic core particles> Step 1 (weighing and mixing): Fe 2 O 3 62.7 copies MnCO 3 29.5 copies Mg(OH) 2 6.8 parts SrCO 3 1.0 copies The ferrite raw materials were weighed so as to obtain the above-mentioned composition ratio, and then crushed and mixed for 5 hours in a dry vibration mill using stainless steel beads with a diameter of 1 / 8 inch.

[0147] Step 2 (Pre-firing): The obtained pulverized material was made into pellets of about 1 mm square using a roller compactor. The pellets were passed through a vibrating sieve with 3 mm openings to remove coarse powder, and then through a vibrating sieve with 0.5 mm openings to remove fine powder. The pellets were then fired in a burner-type firing furnace at 1000°C for 4 hours in a nitrogen atmosphere (oxygen concentration 0.01% by volume) to produce calcined ferrite. The composition of the calcined ferrite obtained was as follows: (MnO) a (MgO) b (SrO) c (Fe 2 O 3 ) d In the above formula, a = 0.257, b = 0.117, c = 0.007, d = 0.393

[0148] Step 3 (Crushing): The obtained calcined ferrite was crushed to about 0.3 mm using a crusher, and then 30 parts of water was added to 100 parts of the calcined ferrite, and the mixture was crushed in a wet ball mill using zirconia beads with a diameter of 1 / 8 inch for 1 hour. The obtained slurry was crushed in a wet ball mill using alumina beads with a diameter of 1 / 16 inch for 4 hours to obtain a ferrite slurry (finely crushed calcined ferrite).

[0149] ·Process 4 (granulation process): To the ferrite slurry, 1.0 part of ammonium polycarboxylate as a dispersant and 2.0 parts of polyvinyl alcohol as a binder were added per 100 parts of calcined ferrite, and the mixture was granulated into spherical particles using a spray dryer (manufacturer: Okawara Kakoki). After adjusting the particle size of the resulting particles, the mixture was heated at 650°C for 2 hours in a rotary kiln to remove the organic components of the dispersant and binder.

[0150] Step 5 (firing): In order to control the firing atmosphere, the material was heated from room temperature to 1300°C in a nitrogen atmosphere (oxygen concentration 1.00% by volume) in an electric furnace over a period of 2 hours, and then fired at 1150°C for 4 hours. The material was then cooled to 60°C over a period of 4 hours, returned from the nitrogen atmosphere to the air, and removed at a temperature of 40°C or less.

[0151] Step 6 (sorting step): After crushing the agglomerated particles, low magnetic particles were removed by magnetic separation, and coarse particles were removed by sieving through a sieve with 250 μm openings to obtain magnetic core particles 1 having a volume distribution standard 50% particle size (D50) of 37.0 μm.

[0152] <Preparation of Coating Resin> A. Cyclohexyl methacrylate monomer 26.8% by mass B. Methyl methacrylate monomer 0.2% by mass C. Methyl methacrylate macromonomer 8.4% by mass (A macromonomer with a weight-average molecular weight of 5000 and a methacryloyl group at one end) D. Toluene 31.3% by mass E. Methyl ethyl ketone 31.3% by mass F. Azobisisobutyronitrile 2.0% by mass Of the above materials, A to D were placed in a four-neck separable flask equipped with a reflux condenser, a thermometer, a nitrogen inlet tube and a stirrer. Nitrogen gas was introduced to replace the inside of the system with nitrogen gas. After that, the system was heated to 80°C, and azobisisobutyronitrile (F) was added and refluxed for 5 hours to polymerize. Hexane was poured into the resulting reaction product to precipitate the copolymer, and the precipitate was filtered and dried in vacuum to obtain coating resin 1. Next, 30 parts of Coating Resin 1 was dissolved in 40 parts of toluene and 30 parts of methyl ethyl ketone to obtain a polymer solution (solid content: 30% by mass).

[0153] <Preparation of coating resin solution> Polymer solution (resin solids concentration 30%) 33.3% by mass Toluene 66.4% by mass Carbon black (Regal 330; manufactured by Cabot Corporation) 0.3% by mass (Primary particle size 25 nm, nitrogen adsorption specific surface area 94 m 2 / g, DBP oil absorption 75mL / 100g) The mixture was dispersed for 1 hour using a paint shaker with zirconia beads having a diameter of 0.5 mm. The resulting dispersion was filtered through a 5.0 μm membrane filter to obtain a coating resin solution.

[0154] <Magnetic carrier manufacturing> (Resin coating process): Magnetic core particles 1 and coating resin solution 1 were put into a vacuum degassing kneader maintained at room temperature (the amount of coating resin solution 1 put in was 2.5 parts as a resin component for 100 parts of magnetic core particles 1). After putting in, the mixture was stirred at a rotation speed of 30 rpm for 15 minutes, and after a certain amount of the solvent (80 mass%) had evaporated, the mixture was heated to 80°C while mixing under reduced pressure, and toluene was distilled off over 2 hours and cooled. The magnetic carrier obtained was separated into low magnetic products by magnetic separation, passed through a sieve with an opening of 70 μm, and then classified with a wind classifier to obtain a magnetic carrier having a 50% particle size (D50) of 38.2 μm based on volume distribution.

[0155] <Production of two-component developer> To 92.0 parts of the magnetic carrier, 8.0 parts of the toner were added and mixed in a V-type mixer (V-20, manufactured by Seishin Enterprise Co., Ltd.) to obtain a two-component developer.

[0156] [evaluation] [Pattern image density unevenness] The prepared electrophotographic photoreceptor and two-component developer were mounted on a modified copy machine of Canon ImageRUNNER ADVANCE C7580II, and the uneven density of the pattern image was evaluated. An A3 test chart with solid black and solid white areas as shown in Figure 2(a) was used. After 10,000 sheets of this test chart were fed continuously, a halftone image with an area ratio of 25% as shown in Figure 2(b) was output. The halftone image density of the solid black and solid white areas corresponding to Figure 2(a) in Figure 2(b) was measured using a reflection densitometer (X-Rite Inc: 504 spectrodensitometer). Specifically, the difference between the average density of 10 points corresponding to the solid black areas and the average density of 10 points corresponding to the solid white areas was calculated. In this evaluation, the relative value was used as the evaluation value when the density difference in Comparative Example 1 was set to 1. The smaller the evaluation value, the better the pattern image density unevenness. The results are shown in Table 4.

[0157] Example 2 In the same manner as in Example 1, the charge transport layer of the electrophotographic photoreceptor was formed, and then the surface layer was formed as follows.

[0158] [Surface layer] 1.65 parts of the copolymer resin was dissolved in a mixed solvent of 40 parts of 1,1,2,2,3,3,4-heptafluorocyclopentane (trade name: Zeorola H, manufactured by Zeon Corporation) and 55 parts of 1-propanol. The copolymer resin used was a copolymer resin having a repeating structural unit represented by the following formula (G) and a repeating structural unit represented by the following formula (H) (weight average molecular weight: 130,000, copolymerization ratio (G) / (H)=1 / 1 (molar ratio)). Thereafter, the liquid to which 23 parts of the polytetrafluoroethylene particles of 1-1 in Table 1 had been added was passed through a high-pressure disperser (product name: Microfluidizer M-110EH, manufactured by Microfluidics, Inc., USA) to obtain a dispersion liquid. after that, 68.0 parts of a hole transporting compound represented by formula (1-6), 2.0 parts of a compound represented by the following formula (J) (manufactured by Sigma-Aldrich), Siloxane-modified acrylic compound, 0.75 parts (BYK-3550, manufactured by BYK Japan Co., Ltd.), 35 parts of 1,1,2,2,3,3,4-heptafluorocyclopentane and 15 parts of 1-propanol are added to the dispersion; The mixture was filtered using a Polyflon filter (product name: PF-040, manufactured by Advantec Toyo Co., Ltd.) to prepare a coating material for the surface layer. The surface layer coating liquid was applied by dip coating on the charge transport layer, and the resulting coating was dried at 40°C for 5 minutes. After drying, the coating was irradiated with an electron beam for 1.6 seconds under a nitrogen atmosphere at an acceleration voltage of 70 KV and an absorbed dose of 15 kGy. Then, the coating was heat-treated for 15 seconds under a nitrogen atmosphere at a temperature of 135°C. The oxygen concentration from the irradiation of the electron beam to the heat treatment for 15 seconds was 15 ppm. Next, the coating was heat-treated for 30 minutes in the atmosphere at a temperature of 105°C to form a surface layer with a thickness of 5 μm. In this way, an electrophotographic photoreceptor was manufactured. [ka] [ka] [ka]

[0159] <Toner manufacturing> (Production of Crystalline Polyester Resin A) Dodecanedioic acid 50 mol parts 1,6-Hexanediol 50 mol parts Octadecanoic acid 5 mol parts The raw monomers and tin(II) octylate (0.5 parts per 100 parts of the total amount of raw monomers) were placed in a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. The temperature was gradually raised to 160°C while stirring under a nitrogen gas atmosphere, and the reaction was carried out at 160°C for 5 hours while stirring. Then, the pressure in the reaction vessel was reduced to 8.3 kPa, and the temperature was raised to 200°C and reacted for 4 hours (first reaction step). Then, the pressure in the reaction vessel was gradually released to return to normal pressure, and 5.0 mol parts of dodecanoic acid were added to 100 mol parts of the total amount of the raw carboxylic acid component and alcohol component, and reacted at 200°C under normal pressure for 2 hours. Then, the pressure in the reaction vessel was reduced to 5 kPa or less again, and the reaction was carried out at 200°C for 3 hours to obtain a crystalline polyester resin A (second reaction step).

[0160] (Production Example of Amorphous Polyester Resin B) A 5L four-neck flask equipped with a nitrogen inlet tube, a cooling tube, a stirrer, and a thermocouple was replaced with nitrogen, and tin(II) octylate was added and heated to 180°C, followed by reaction for 10 hours. After further reaction for 5 hours at 15mmHg (first reaction step), trimellitic anhydride was added according to Table 4 as the second reaction step, followed by reaction for 3 hours at 180°C to obtain amorphous polyester resin B.

[0161] (Production Example of Amorphous Polyester Resin C) Amorphous polyester resin C was produced in the same manner as in the production example of amorphous polyester resin B, except that the raw materials shown in Table 3 were used and the reaction was stopped in the second reaction step when it was confirmed that the softening point had reached the temperature shown in Table 3.

[0162] [Table 3]

[0163] In Table 3, the abbreviations have the following meanings: BPA-PO: Propylene oxide adduct of bisphenol A BPA-EO: Ethylene oxide adduct of bisphenol A TPA: Terephthalic acid TMA anhydride: trimellitic anhydride.

[0164] next Crystalline polyester resin A 15.0 parts Amorphous polyester resin B 62.5 parts Amorphous polyester resin C 30.0 parts Hydrocarbon wax (Nippon Seiro Co., Ltd.: FNP0090) 5.0 parts Cyan pigment (Dainichi Seika: Pigment Blue 15:3) 7.0 parts 0.3 parts of 3,5-di-t-butylsalicylic acid aluminum compound The above materials were mixed in a Henschel mixer (FM-75, manufactured by Mitsui Mining Co., Ltd.) at a rotation speed of 20 s. -1After mixing for a rotation time of 5 minutes, the mixture was melt-kneaded in a twin-screw kneader (PCM-30, manufactured by Ikegai Corporation) set at a temperature of 145°C. The kneaded product was cooled and coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed product. The coarsely crushed product was finely crushed using a mechanical crusher (T-250, manufactured by Turbo Kogyo Co., Ltd.). The product was further classified using Faculty F-300 (manufactured by Hosokawa Micron Corporation) to obtain toner particles. 100 parts toner particles Hydrophobic silica particles surface-treated with hexamethyldisilazane (BET: 200m 2 / g)1.0 copies 1.0 part of strontium titanate No. 1 in Table 2 The above materials were mixed in a Henschel mixer (FM-75, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) at a rotation speed of 30 s. -1 The mixture was mixed at a rotation time of 10 minutes to obtain a toner. Other than that, a two-component developer was prepared in the same manner as in Example 1. The prepared electrophotographic photoreceptor and two-component developer were used to carry out the same evaluation as in Example 1. The results are shown in Table 4.

[0165] Example 3 An electrophotographic photoreceptor was prepared in the same manner as in Example 2, except that the amount of polytetrafluoroethylene particles in the surface layer was changed to 7.7 parts. The produced electrophotographic photoreceptor and the two-component developer produced in Example 1 were used to carry out the same test as in Example 1. The results are shown in Table 4.

[0166] Example 4 An electrophotographic photoreceptor was prepared in the same manner as in Example 2, except that the amount of polytetrafluoroethylene particles in the surface layer was changed to 46 parts. The produced electrophotographic photoreceptor and the two-component developer produced in Example 1 were used to carry out the same test as in Example 1. The results are shown in Table 4.

[0167] Example 5 An electrophotographic photoreceptor was prepared in the same manner as in Example 2, except that the amount of polytetrafluoroethylene particles in the surface layer was changed to 5.2 parts. The produced electrophotographic photoreceptor and the two-component developer produced in Example 1 were used to carry out the same test as in Example 1. The results are shown in Table 4.

[0168] Example 6 An electrophotographic photoreceptor was prepared in the same manner as in Example 2, except that the amount of polytetrafluoroethylene particles in the surface layer was changed to 52 parts. The produced electrophotographic photoreceptor and the two-component developer produced in Example 1 were used to carry out the same test as in Example 1. The results are shown in Table 4.

[0169] Example 7 An electrophotographic photoreceptor was produced in the same manner as in Example 2, except that the polytetrafluoroethylene particles in the surface layer were changed to No. 2 in Table 1 and the number of parts was changed to 52. The produced electrophotographic photoreceptor and the two-component developer produced in Example 1 were used to carry out the same test as in Example 1. The results are shown in Table 4.

[0170] Example 8 An electrophotographic photoreceptor was produced in the same manner as in Example 2, except that the polytetrafluoroethylene particles in the surface layer were changed to No. 3 in Table 1 and the number of parts was changed to 52. The produced electrophotographic photoreceptor and the two-component developer produced in Example 1 were used to carry out the same test as in Example 1. The results are shown in Table 4.

[0171] Example 9 An electrophotographic photoreceptor was produced in the same manner as in Example 2, except that the polytetrafluoroethylene particles in the surface layer were changed to No. 4 in Table 1 and the number of parts was changed to 52. A two-component developer was prepared under the same conditions as in Example 1, except that strontium titanate No. 2 in Table 2 was used. The produced electrophotographic photoreceptor and two-component developer were used to carry out the same evaluation as in Example 1. The results are shown in Table 4.

[0172] Example 10 Under the same conditions as in Example 9, an electrophotographic photoreceptor was prepared. A two-component developer was prepared under the same conditions as in Example 1, except that strontium titanate No. 3 in Table 2 was used. The prepared electrophotographic photoreceptor and two-component developer were used to carry out the same evaluation as in Example 1. The results are shown in Table 4.

[0173] Example 11 An electrophotographic photoreceptor was produced in the same manner as in Example 2, except that the polytetrafluoroethylene particles in the surface layer were changed to No. 5 in Table 1 and the number of parts was changed to 52. A two-component developer was prepared under the same conditions as in Example 1, except that strontium titanate No. 2 in Table 2 was used. The prepared electrophotographic photoreceptor and two-component developer were used to carry out the same evaluation as in Example 1. The results are shown in Table 4.

[0174] Example 12 Under the same conditions as in Example 11, an electrophotographic photoreceptor was prepared. A two-component developer was prepared under the same conditions as in Example 1, except that strontium titanate No. 3 in Table 2 was used. The prepared electrophotographic photoreceptor and two-component developer were used to carry out the same evaluation as in Example 1. The results are shown in Table 4.

[0175] Comparative Example 1 Under the same conditions as in Example 8, an electrophotographic photoreceptor was produced. A two-component developer was prepared under the same conditions as in Example 1, except that strontium titanate No. 4 in Table 2 was used. The prepared electrophotographic photoreceptor and two-component developer were used to carry out the same evaluation as in Example 1. The results are shown in Table 4.

[0176] Comparative Example 2 An electrophotographic photoreceptor was produced in the same manner as in Example 2, except that the polytetrafluoroethylene particles in the surface layer were changed to No. 6 in Table 1 and the number of parts was changed to 52. A two-component developer was prepared under the same conditions as in Example 1. The prepared electrophotographic photoreceptor and two-component developer were used to carry out the same evaluation as in Example 1. The results are shown in Table 4.

[0177] Comparative Example 3 An electrophotographic photoreceptor was produced in the same manner as in Example 2, except that the polytetrafluoroethylene particles in the surface layer were changed to No. 7 in Table 1 and the number of parts was changed to 52. A two-component developer was prepared under the same conditions as in Example 1. The prepared electrophotographic photoreceptor and two-component developer were used to carry out the same evaluation as in Example 1. The results are shown in Table 4.

[0178] Comparative Example 4 Under the same conditions as in Comparative Example 2, an electrophotographic photoreceptor was produced. A two-component developer was prepared under the same conditions as in Example 1, except that strontium titanate No. 5 in Table 2 was used. The prepared electrophotographic photoreceptor and two-component developer were used to carry out the same evaluation as in Example 1. The results are shown in Table 4.

[0179] Comparative Example 5 Under the same conditions as in Example 8, an electrophotographic photoreceptor was produced. A two-component developer was prepared under the same conditions as in Example 1, except that titanium oxide having a particle size of 50 nm was used instead of the strontium titanate particles. The prepared electrophotographic photoreceptor and two-component developer were used to carry out the same evaluation as in Example 1. The results are shown in Table 4.

[0180] [Table 4] It is apparent from Examples 1 to 12 and Comparative Examples 1 to 5 that the effects of the present invention are obtained. [Explanation of symbols]

[0181] 101 Support 102 Undercoat layer 103 Charge generating layer 104 Charge transport layer 105 Surface layer 1. Electrophotographic photoreceptor 2-axis 3. Charging means 4 Image exposure light 5. Developing method 6 Transfer Method 7 Transfer material 8 Fixing Method 9 Cleaning Method 10 Pre-exposure light 11 Process cartridge 12 Guidance means

Claims

1. an electrophotographic photoreceptor having a support, a photosensitive layer, and a surface layer; a charging means for charging the surface of the electrophotographic photoreceptor; an image exposure means for irradiating the charged surface of the electrophotographic photosensitive member with image exposure light to form an electrostatic latent image on the surface of the electrophotographic photosensitive member; a developing means having a toner and for developing the electrostatic latent image with the toner to form a toner image on the surface of the electrophotographic photoreceptor; a transfer means for transferring the toner image from the surface of the electrophotographic photoreceptor to a transfer material; a cleaning means for removing residual toner remaining on the surface of the electrophotographic photoreceptor after transfer by a cleaning blade; a fixing means for fixing the toner image transferred onto the transfer material; An image forming apparatus having The surface layer is a charge transporting compound having a chain polymerizable functional group or a step-polymerizable functional group; Polytetrafluoroethylene particles; A cured film obtained by curing a composition comprising: The polytetrafluoroethylene particles have a number average particle diameter of primary particles of 165 nm or more and 185 nm or less, The toner has toner particles and strontium titanate particles present on the surfaces of the toner particles, The strontium titanate particles have a number average particle size of 20 nm or more and 70 nm or less.

2. 2. The image forming apparatus according to claim 1, wherein the proportion of polytetrafluoroethylene particles having a primary particle diameter of 150 nm or less is 10% or more, and the proportion of polytetrafluoroethylene particles having a primary particle diameter of 250 nm or more is 5% or less, among the polytetrafluoroethylene particles.

3. 3. The image forming apparatus according to claim 1, wherein the content of the polytetrafluoroethylene particles in the surface layer is from 10% by mass to 40% by mass with respect to the total mass of the surface layer.

4. 4. The image forming apparatus according to claim 1, wherein the charge transporting compound has a hydroxy group, a hydroxymethyl group, or an alkoxymethyl group.

5. a charging step of charging the surface of an electrophotographic photoreceptor; an image exposure step of irradiating the charged surface of the electrophotographic photoreceptor with image exposure light to form an electrostatic latent image on the surface of the electrophotographic photoreceptor; a developing step of developing the electrostatic latent image with a toner to form a toner image on the surface of the electrophotographic photoreceptor; a transfer step of transferring the toner image from the surface of the electrophotographic photoreceptor to a transfer material; a cleaning step of removing residual toner remaining on the surface of the electrophotographic photoreceptor after the transfer step by a cleaning blade; a fixing step of fixing the toner image transferred onto the transfer material; An image forming method comprising the steps of: The electrophotographic photoreceptor has a support, a photosensitive layer, and a surface layer, The surface layer is a charge transporting compound having a chain polymerizable functional group or a step-polymerizable functional group; Polytetrafluoroethylene particles; A cured film obtained by curing a composition comprising: The polytetrafluoroethylene particles have a number average particle diameter of primary particles of 165 nm or more and 185 nm or less, The toner has toner particles and strontium titanate particles present on the surfaces of the toner particles, The number average particle size of the primary particles of the strontium titanate particles is 20 nm or more and 70 nm or less.

1. An image forming method comprising:

6. An electrophotographic photoreceptor having a support, a photosensitive layer, and a surface layer, a charging means for charging the surface of the electrophotographic photoreceptor; a developing means having a toner and for developing the electrostatic latent image with the toner to form a toner image on the surface of the electrophotographic photoreceptor; a transfer means for transferring the toner image from the surface of the electrophotographic photoreceptor to a transfer material; and a cleaning means for removing residual toner remaining on the surface of the electrophotographic photoreceptor after transfer by means of a cleaning blade; A process cartridge having at least one means selected from the group consisting of: The process cartridge is detachably mountable to a main body of an electrophotographic apparatus, The surface layer is a charge transporting compound having a chain polymerizable functional group or a step-polymerizable functional group; Polytetrafluoroethylene particles; A cured film obtained by curing a composition comprising: The polytetrafluoroethylene particles have a number average particle diameter of primary particles of 165 nm or more and 185 nm or less, The toner comprises toner particles and strontium titanate particles present on the surfaces of the toner particles, The number average particle size of the primary particles of the strontium titanate particles is 20 nm or more and 70 nm or less. A process cartridge comprising:

7. 7. The process cartridge according to claim 6, wherein, among said polytetrafluoroethylene particles, a content ratio of polytetrafluoroethylene particles having a primary particle diameter of 150 nm or less is 10% or more, and a content ratio of polytetrafluoroethylene particles having a primary particle diameter of 250 nm or more is 5% or less.

8. 8. The process cartridge according to claim 6, wherein a content of said polytetrafluoroethylene particles in said surface layer is from 10% by mass to 40% by mass based on a total mass of said surface layer.

9. 9. The process cartridge according to claim 6, wherein the charge transporting compound has a hydroxy group, a hydroxymethyl group, or an alkoxymethyl group.

Citation Information

Patent Citations

  • Electrophotographic photoreceptor, process cartridge, and electrophotographic device

    JP2004037740A

  • Electrophotographic apparatus, process cartridge and facsimile machine

    JP2005091498A

  • Organic photoreceptor, manufacturing method thereof, and process cartridge and image forming device using the organic photoreceptor

    JP2005275373A

  • Image forming method

    JP2006195155A

  • Nonmagnetic one-component toner for development

    JP2008058521A